The Importance Of Humanism Education For Primary School Children In The 21st Century Globalization Era - Firmansyah, Akmal; Yudha, Muhamad; Suyato, Suyato; Sukarti, Sri Endang Edi (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2024)
This article discusses the importance of humanism education for primary school children in the 21st century era of globalization. In the context of globalization, children face complex challenges that require adaptive social, emotional and cultural skills. Humanism education offers an approach that can build character, empathy and tolerance, and increase multicultural awareness. The purpose of this study was to explore the implementation strategies, challenges, and solutions in implementing humanism education in elementary schools. The research method used was a qualitative approach with a case study in an elementary school that implemented a humanism approach.Data were obtained through participatory observation, in-depth interviews with teachers and students, and analysis of curriculum and education policy documents. The sample selection was purposive, focusing on schools with good humanism practices. The results showed that the integration of humanism values in the curriculum, teacher training, and community support were key to successful implementation. The main challenges included a curriculum focused on standardized tests, limited resources and resistance from various parties. However, support from the government, ongoing teacher training and community involvement can overcome these barriers. In conclusion, humanism education is important to prepare children for the dynamics of globalization, build strong character, and create an inclusive and supportive learning environment.